2010
DOI: 10.1007/s10682-010-9445-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia drives plastic divergence in cichlid body shape

Abstract: Organisms experience multiple selective agents that can influence phenotypes through heritable and/or plastic changes, often reflecting complex interactions between phenotype and environment. Environmental factors can directly influence phenotypes, but also indirectly affect phenotypic variation when genetic/plastic change in one trait results in correlated genetic/plastic change in another trait. In fishes, body shape is a trait that might be particularly prone to influence from environmental pressures that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 44 publications
2
33
1
Order By: Relevance
“…Indeed, within the constricted space of the head, larger eyes are mostly correlated with shorter snouts and shorter premaxillary pedicels (Barel, 1983;Crispo & Chapman, 2010). The two populations examined differ from each other in a few measurements on the head, and head morphology in particular is known to display responses to a changing environment in 'Haplochromis' species, which has been demonstrated under experimental (e.g.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Indeed, within the constricted space of the head, larger eyes are mostly correlated with shorter snouts and shorter premaxillary pedicels (Barel, 1983;Crispo & Chapman, 2010). The two populations examined differ from each other in a few measurements on the head, and head morphology in particular is known to display responses to a changing environment in 'Haplochromis' species, which has been demonstrated under experimental (e.g.…”
Section: Discussionmentioning
confidence: 83%
“…Crispo & Chapman, 2010;van Rijssel & Witte, 2013;Fig. 5 Principal component analysis plot of PC2 against PC1 for a PCA on 19 log-transformed measurements (n = 64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental factors can either directly influence body proportions or indirectly affect morphometric variation, when changes in one trait result in correlated changes in others (Crispo & Chapman, 2011). The correlation among morphological traits is timedependent and displays high developmental plasticity (Grunbaum et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The correlation among morphological traits is timedependent and displays high developmental plasticity (Grunbaum et al, 2007). It has been demonstrated that environmental factors such as current velocity, oxygen concentration, water temperature, and salinity may have a significant effect on fish morphotype (Mahon, 1984;Imre et al, 2002;Grunbaum et al, 2007;Paez et al, 2008;Crispo & Chapman, 2011;Franssen et al, 2012;Rajput et al, 2013).…”
Section: Introductionmentioning
confidence: 99%